Cerebral arteriovenous malformations in the era of embolization for angiographic cure: a single-center experience in Egypt - Mohamed K Elewa (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2018)
Abstract Background Embolization for cerebral arteriovenous malformations (AVMs) has evolved in the last decade with evolution in both equipment and material. Embolization targets have expanded to include angiographic cure. Methods To discuss the technical and management outcomes of our first cerebral AVM case series treated with embolization. The clinical, angiographic, treatment, and outcome variables of consecutive cerebral arteriovenous malformation cases, treated with curative embolization, between January 2011 and June 2017 in one regional center, were retrospectively analyzed. Results In 21 patients, 21 AVMs were identified, and 13 patients (61.9%) were males. The mean of the age was 34.24 ± 12.99. Fifteen patients (71.4%) had a history of intracranial hemorrhage, and 10 (47.6%) patients had seizures. Sixteen patients (76.2%) were at grade 1 of modified Rankin Scale (mRS) at admission. The median for modal Spetzler-Martin grade was 2. The average number of arterial feeders was 3. Direct arteriovenous fistulas were found in 4 cases (19.0%). Venous aneurysms were found in 4 cases (19.0%). Seventeen AVMs (80.9%) were considered high bleeding risk lesions. Forty-three embolization sessions were done. Early hemorrhage occurred in 3 sessions (7.0%). Vessel perforation occurred 1 session (2.3%). Poor outcome occurred in 1 patient that was discharged at grade 3 mRS. Angiographic cure was achieved in 9 patients (42.9%). The average size reduction was 65%. Conclusions Onyx embolization could serve as a curative option for AVM treatment with accepted morbidity and mortality.